Dual targeting delivery of miR-328 by functionalized mesoporous silica nanoparticles for colorectal cancer therapy. (7th August 2018) - Li, Yang; Duo, Yanhong; Zhai, Peng; He, Lisheng; Zhong, Keli; Zhang, Yue; Huang, Kaibin; Luo, Jinfeng; Zhang, Han; Yu, Xiaofang
Aim: We aim to explore the regulatory mechanism of miR-328 and further develop miR-328-loaded mesoporous silica nanoparticles (MSNs) and surface-decorated with polymerized dopamine, epithelial cell adhesion molecule aptamer and bevacizumab for the dual-targeting treatment of colorectal cancer (CRC).Materials & methods: The relationship between miR-328 and CPTP and the mechanism and antitumor effect of MSNs-miR-328@PDA-PEG-Apt-Bev were evaluated.Results: We found CPTP is a direct target of miR-328. Compared with other groups, MSNs-miR-328@PDA-PEG-Apt-Bev can significantly increase the level of miR-328 and inhibit the expression of CPTP in SW480 cells. The results exhibit this multifunctional bioconjugates can achieve an increased binding ability and much higher cytotoxicity to CRC both in vitro and in vivo .Conclusion: This multifunctional nanoplatform is a promising miRNA replacement therapy for CRC.